Reproductive Performance of Imported Jersey Cows in Malaysia - Marimuthu, Murugaiyah (1982)
Several criteria of reproductive efficiency for 102 imported pregnant Jersey heifers were analysed from April 1978 to December 1980 at the Malaysian Agricultural Research and Development Institute, Serdang. Significant differences in the reproductive efficiency was observed among the three reproductive periods (RP). An outbreak of babesiosis was a major cause of mortality in the pregnant heifers within a month of importation. Abortions (33.3 %), the major reproductive disorder in RP 1, was associated with either heat stress and/or babesiosis. Calving to oestrus,calving to conception and calving interval for RP 2 was 75.1 ± 3.1; 228.3 ± 12.1 and 507.9 ± 12.1 days respectively while for RP 3 , it was 38.8 ± 3.5; 94.6 ± 8.4; and 352.3 ± 5.8 days respectively. Mean services per conception was 4002 ± 0.3 and 1.93 ± 0.2 for RP 2 and RP 3 respectively. Conception rates (CR) for all services were correlated (p< 0.01) with minimum temperature, (r = -0.89). maximum temperature, (r = -0.95) and humidity, (r = -0.94). At the average temperature-humidity index (THI) below 76.5 on the day of insemination, the CR for 89 cows waS 64% compared to 14% for 325 cows bred at THI above 76.5. The THI for the day of insemination was found to be most critical to conception. The influence of environmental temperature and relative humidity on CR was studied in 27 Jersey cows calving normally. Cows after insemination were assigned to one of three environment conditions: (a) in paddock, (b) in shed, (c) in shed with water sprinkling. Highest environmental temperature and rectal temperature was recorded in cows in the paddocks and lowest in animals kept in Shed with water sprinkling. Relative humidity was highest in the shed with water sprinkling. Conception rate was 0% (paddock); 56% (shed) and 78% (in shed with water sprinkling). Oestrous cycle lengths were shorter (16.5 ± 0.4 days) for cows in the paddock compared to those in the sheds (20. 5 + 0.3 days) . The present study indicated that high environmental temperature and humidity was associated with the reduced fertility in Jersey cows. However, the reproductive performance of Jersey cows improved as they adapted to the tropical climate. Protecting cows from any factor causing an elevated rectal temperature around the time of insemination improved conception rates.